2023
DOI: 10.3847/2041-8213/ad0ed9
|View full text |Cite
|
Sign up to set email alerts
|

Water-rich Disks around Late M Stars Unveiled: Exploring the Remarkable Case of Sz 114

Chengyan Xie,
Ilaria Pascucci,
Feng Long
et al.

Abstract: We present an analysis of the JDISCS JWST/MIRI-MRS spectrum of Sz 114, an accreting M5 star surrounded by a large dust disk with a shallow gap at ∼39 au. The spectrum is molecule-rich; we report the detection of water, CO, CO2, HCN, C2H2, and H2. The only identified atomic/ionic transition is from [Ne ii] at 12.81 μm. A distinct feature of this spectrum is the forest of water lines with the 17.22 μm emission surpassing that of most mid-to-late M star disks by an order of magnitude in flux and aligning instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Infrared observations have shown that the ratio of molecular emission lines from C 2 H 2 and HCN is <1 in disks around higher-mass stars and >1 in disks around VLMSs, indicating differences in composition and evolution of the gas ( 10 ). Weak or undetected lines of H 2 O indicate that those disks typically have a high C/O ratio ( 11 ), but there is one known exception with strong H 2 O emission ( 12 ). The observation of a VLMS with a C 2 H 2 /H 2 O ratio several orders of magnitude higher than previously inferred has been interpreted as being caused by C/O enhancement through the destruction of carbon-rich dust grains, which would affect the bulk composition of any planets forming in the disk ( 13 ).…”
mentioning
confidence: 99%
“…Infrared observations have shown that the ratio of molecular emission lines from C 2 H 2 and HCN is <1 in disks around higher-mass stars and >1 in disks around VLMSs, indicating differences in composition and evolution of the gas ( 10 ). Weak or undetected lines of H 2 O indicate that those disks typically have a high C/O ratio ( 11 ), but there is one known exception with strong H 2 O emission ( 12 ). The observation of a VLMS with a C 2 H 2 /H 2 O ratio several orders of magnitude higher than previously inferred has been interpreted as being caused by C/O enhancement through the destruction of carbon-rich dust grains, which would affect the bulk composition of any planets forming in the disk ( 13 ).…”
mentioning
confidence: 99%